The Impact of Virtual Physical Education on Physical Activity and the Reduction of Sedentary of Elementary Students in the Covid-19 Era - Halil Bisgin (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aims: Preliminary evidence suggests that the social constraints needed to reduce the prevalence of COVID-19 have increased participation in sedentary behavior and reduced children’s opportunities to participate in physical activity. Therefore, the aim of the present study was the effect of virtual physical education on physical activity and reduction of sedentary of elementary students in the Covid-19 era. Materials and Methods: A Semi-experimental design was conducted (pre-test and post-test) with two experimental and control groups. For this purpose, thirty 8 to 11 year old male students in Kütahya who had low scores in the Physical Activity Questionnaire (PAQ-C) (1 to 2.33) and high scores in the Inactive Researcher’s Questionnaire, were selected by convenience sampling and randomly assigned to experimental and control groups (equal to 15 people in each group). Then, the experimental group underwent virtual physical education training for 10 sessions and two 45-minute sessions each week. No intervention was performed on the control group during this period. All subjects completed the Physical Activity Questionnaire (PAQ-C) and the sedentary researcher-made questionnaire before and after the training. Univariate analysis of covariance was used to analyze the data. Results: The results showed that there was a significant difference between the level of physical activity and sedentary of elementary students in the experimental and control groups. The intensity of the effect is equal to 0.58 and 0.66, respectively. The amount of physical activity in the experimental group (m = 2.57) was significantly higher than the control group (m = 1.95). The rate of sedentary in the experimental group (m = 3.25) was significantly lower than the control group (m = 3.64). Conclusion: The results showed that virtual training of physical training (watching video models and teaching the basic concepts of physical activity) is effective in increasing physical activity and reducing sedentariness of 8 to 11 year old male students during COVID-19.